Antibacterial and osteoinductive properties of wollastonite scaffolds impregnated with propolis produced by additive manufacturing (2023)
Biocompatible ceramic scaffolds offer a promising approach to address the challenges in bone reconstruction. Wollastonite, well-known for its exceptional biocompatibility, has attracted significant attention in orthopedics and craniofacial fields. However, the antimicrobial properties of wollastonite have contradictory findings, necessitating further research to enhance its antibacterial characteristics. This study aimed to explore a new approach to improve in vitro biological response in terms of antimicrobial activity and cell proliferation by taking advantage of additive manufacturing for the development of scaffolds with complex geometries by 3D printing using propolis-modified wollastonite. The scaffolds were designed with a TPMS (Triply Periodic Minimal Surface) gyroid geometric shape and 3D printed prior to impregnation with propolis extract. The paste formulation was characterized by rheometric measurements, and the presence of propolis was confirmed by FTIR spectroscopy. The scaffolds were omprehensively assessed for their mechanical strength. The biological characterization involved evaluating the antimicrobial effects against Staphylococcus aureus and Staphylococcus epidermidis, employing Minimum Inhibitory Concentration (MIC), Zone of Inhibition (ZOI), and biofilm formation assays. Additionally, SaOs-2 cultures were used to study cell proliferation (Alamar blue assay), and potential osteogenic was tested (von Kossa, Alizarin Red, and ALP stainings) at different time points. Propolis impregnation did not compromise the mechanical properties of the scaffolds, which exhibited values comparable to human trabecular bone. Propolis incorporation conferred antibacterial activity against both Staphylococcus aureus and Staphylococcus epidermidis. The implementation of TPMS gyroid geometry in the scaffold design demonstrated favorable cell proliferation with increased metabolic activity and osteogenic potential after 21 days of cell cultures.